2013
DOI: 10.2190/ec.48.3.d
|View full text |Cite
|
Sign up to set email alerts
|

Student Laptop Use and Scores on Standardized Tests

Abstract: Objectives:The primary objective of the study was to investigate the relationship between ubiquitous laptop use and academic achievement. It was hypothesized that students with ubiquitous laptops would score on average higher on standardized tests than those without such computers. Methods: Data were obtained from two sources. First, demographic and computer usage information was obtained through face-to-face interviews of 4th and 5th grade students enrolled in an ethnically diverse elementary school in Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Positive results in ELA were also reported in additional studies not included in the meta-analysis because insufficient statistical information was provided for computing effect size (e.g., Bebell & Kay, 2010;Kposowa & Valdez, 2013;Zheng, Warschauer, & Farkas, 2013). For example, Bebell and Kay (2010) found that eighth-grade students in laptop classroom environments had higher ELA score growth than their comparison peers within 2 years of implementation of the laptop program, based on the Massachusetts Comprehensive Assessment System test.…”
Section: English Language Artsmentioning
confidence: 96%
“…Positive results in ELA were also reported in additional studies not included in the meta-analysis because insufficient statistical information was provided for computing effect size (e.g., Bebell & Kay, 2010;Kposowa & Valdez, 2013;Zheng, Warschauer, & Farkas, 2013). For example, Bebell and Kay (2010) found that eighth-grade students in laptop classroom environments had higher ELA score growth than their comparison peers within 2 years of implementation of the laptop program, based on the Massachusetts Comprehensive Assessment System test.…”
Section: English Language Artsmentioning
confidence: 96%
“…The field of educational and instructional technology focuses on issues of technology adoption and integration through studies that address faculty attitudes (Marzilli et al , ; Smith, ), students perceptions of technology in higher education (Parker, Bianchi & Cheah, ), and even preservice teacher perceptions of technology and innovation in the classroom (Ajayi, ). Studies that address impacts on student achievement are also prevalent in higher education (Castillo‐Merino & Serradell‐López, ) and K‐12 settings (Kposowa & Valdez, ; Lei & Zhao, ). Yet rarely are questions raised about how individual educators understand and define innovation in their teaching and use of technology.…”
Section: Introductionmentioning
confidence: 99%
“…In an evaluation of the Texas one-to-one Technology Immersion Pilot (TIP) project, Shapely et al 2009 Lowther et al (2003) showed similar results for sixth and seventh grade students in 61 schools across Florida, including a positive relationship between participation in the one-to-one technology initiative and mathematics achievement. In a more recent study, Kposowa and Valdez (2013) found that California students who were placed in a one-to-one laptop initiative classroom had significantly higher academic performance in English, mathematics, and science than students not participating in the one-to-one technology program.…”
Section: Effects Of One-to-one Technology Initiatives On Student Acadmentioning
confidence: 97%